Penerapan Flipped Learning pada Materi Metode Squash pada Mata Kuliah Mikroteknik - Puspita Ratna Susilawati (Universitas Muhammadiyah Prof. Dr. Hamka, 2020)
Background: The implementation of flipped learning could be one of the solutions offered so that practicum that was limit by time could be carried out. This study aimed to determine the effect of implementing the flipped learning model on student understanding of the squash method material in microtechnique courses. Methods: This quasi study used a non-equivalent control group design. In the treatment group the flipped learning model was applied and an analysis of its effect on student understanding was carried out. The research data were obtained through the pretest and posttest. The pretest is used to evaluate the ability to remembering and understanding, while the posttest evaluates the ability to analyze, evaluate and create. The pretest and posttest value data were used to calculate the N-gain value, then the Mann-Whitney U test was performed to determine the difference between the two. Results: The increase in the mean value in the treatment class was higher than in the control class. The treatment class was 5.2, while the control class was 0.82. The percentage of students who showed a high and moderate N-gain score in the treatment class was 54.05%, while the control class was 40%. There was no difference between the N-gain value in the treatment and control classes. The flipped learning model's implementation did not affect student understanding but had been able to increase student understanding of the squash method material. Conclusions: The flipped learning model could be applied as a solution to practical problems constrained by time constraints.